1990
DOI: 10.1002/gepi.1370070303
|View full text |Cite
|
Sign up to set email alerts
|

Familial resemblance of plasma apolipoprotein B: The Nancy study

Abstract: The familial resemblance of plasma apolipoprotein B (apo B) was investigated in a sample of 102 families including 419 members who volunteered for a free health checkup in the Preventive Center of Vandoeuvre-lès-Nancy, France. The mean levels (+/- SD) of apo B were 141.0 (+/- 32.6), 121.8 (+/- 27.7), and 98.6 (+/- 22.6) mg/dl in fathers, mothers, and offspring, respectively. The familial correlations were 0.04, 0.13, 0.21 (P less than .01), and 0.47 (P less than .001) between spouses, father-offspring, mother-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…This estimated correla tion is comparable to that reported by others (0.13 to 0.47).23,24 Although examined in completely different study populations, most studies reported a codom inant m odel as the most parsim onious fit on their apoB data.20'22,24,25,31 A few studies, however, preferred a dom inant or recessive m odel. 19,23,26 The estimated rela tive frequency of the "lo w " apoB allele at 66% is in agreement with other reports.2 1 1 '22,24,25,31 These consis tent findings suggest that genetic control o f apoB levels is comparable in subjects with different dyslipidem ia phenotypes. Some o f the remaining differences in the results may be explained by the large differences in …”
Section: Discussionsupporting
confidence: 87%
“…This estimated correla tion is comparable to that reported by others (0.13 to 0.47).23,24 Although examined in completely different study populations, most studies reported a codom inant m odel as the most parsim onious fit on their apoB data.20'22,24,25,31 A few studies, however, preferred a dom inant or recessive m odel. 19,23,26 The estimated rela tive frequency of the "lo w " apoB allele at 66% is in agreement with other reports.2 1 1 '22,24,25,31 These consis tent findings suggest that genetic control o f apoB levels is comparable in subjects with different dyslipidem ia phenotypes. Some o f the remaining differences in the results may be explained by the large differences in …”
Section: Discussionsupporting
confidence: 87%
“…Again, in addition to potential factors discussed above, limited sample size might also be an explanation that prevented the second distribution component from being detectable in this study. For apo B-100, studies in a large Amish pedigree ascertained through a 13-year-old boy who died suddenly of advanced coronary atherosclerosis 24 and in a sample of 102 families volunteered for a free health checkup in the Preventive Center of Vandoeuvre-lès-Nancy of France 25 found no evidence of a major-gene effect, but a multifactorial component was significant. In contrast, 6 studies reported positive findings of a major gene influencing apo B-100 levels.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In contrast to these positive findings, there also have been contradictory reports for apo A-1 9,18,23 and apo B-100. 24,25 Prospective epidemiological studies have provided evidence that apolipoprotein levels can be affected by physical activity and fitness levels. 26 In particular, apo A-1 levels have been reported to increase and apo B-100 levels to decrease 27,28 in response to exercise training.…”
mentioning
confidence: 99%
“…The linkage disequilibrium coefficient (D 0 ) between the two PAI-1 polymorphisms was estimated by using loglinear model analysis [26]. PCOS women carrying the combination of the -844 A/A and non-5G/5G genotypes, or the coadunation of PAI-1 4G/4G and -844 non-G/G genotype, had significantly higher plasma PAI-1 levels than normal controls.…”
Section: Discussionmentioning
confidence: 99%